APPROCHE SOCIOMETRIQUE DE L’AFFECTIVITE CHEZ LES JEUNES SCOLARISES AU DEBUT DE L’ADOLESCENCE - MATSORO Amédée (IJRDO- Journal of Educational Research, 2024)
This field research solicited the participation of 66 pre-adolescents aged 12 to 13, including 41 boys and 25 girls, all in school. Thanks to a sociometric questionnaire, they made 283 choices and 244 rejections. From the analysis of the data, it emerges that there is no correlation between sociometric status, expressed by the choices received and academic performance in mathematics. There would be other factors that would lead to choosing one subject more than another.